2022
DOI: 10.1186/s12894-022-01133-1
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of lower urinary tract symptoms in diabetic patients: a cross-sectional study

Abstract: Background Lower urinary tract symptoms (LUTS) are common among diabetic patients and represent hidden and mysterious morbidity. The pathophysiology of LUTS among diabetes mellitus (DM) patients is multifactorial. Importantly, LUTS is known to cause physical and psychological distress. Thus, this study describes LUTS among DM patients, investigates factors that may associate with it, and assesses the possible relationship between LUTS and the quality of life of diabetics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…On the other hand, the correlation between LUTS/BPH and obesity remains controversial. While many studies reinforce the idea that obesity increases the risk of BPH and LUTS ( Kim et al, 2021 ; Chen et al, 2022 ; Qasrawi et al, 2022 ; Wang et al, 2022 ), others have reported a similar pattern of voiding function in lean, overweight, and obese patients ( Bauer et al, 2022 ). In a previous report ( Calmasini et al, 2017 ), we showed that obesity caused prostate hyperplasia, insulin resistance, and greater contractile responses to a 1 -adrenoceptor agonists.…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, the correlation between LUTS/BPH and obesity remains controversial. While many studies reinforce the idea that obesity increases the risk of BPH and LUTS ( Kim et al, 2021 ; Chen et al, 2022 ; Qasrawi et al, 2022 ; Wang et al, 2022 ), others have reported a similar pattern of voiding function in lean, overweight, and obese patients ( Bauer et al, 2022 ). In a previous report ( Calmasini et al, 2017 ), we showed that obesity caused prostate hyperplasia, insulin resistance, and greater contractile responses to a 1 -adrenoceptor agonists.…”
Section: Discussionmentioning
confidence: 90%
“…Factors such as not engaging in exercise, HTN, and DM were associated with higher IIQ-7 scores, indicating a greater impact of UI on daily activities. Managing these modifiable risk factors may positively influence the overall impact of UI on daily life [ 18 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our group has published several papers about lower urinary tract symptoms (LUTS) and UI among different cohorts of patients in Palestine [18][19][20][21][22]. This was a national study investigating the prevalence of UI and the factors that influence it.…”
Section: Introductionmentioning
confidence: 99%
“…A score that is equal to or greater than 8 indicates the presence of clinically significant LUTS. The IPSS values were classified as mild (scores 0-7), moderate (scores [8][9][10][11][12][13][14][15][16][17][18][19], and severe (scores 20-35) LUTS. Furthermore, the IPSS incorporates an 8th question, a quality-of-life assessment, in the form of a single 7-point scale question, inquiring about the patient's hypothetical feelings if they were to live with their current urinary condition for the rest of their life.…”
Section: The International Prostate Symptom Score (Ipss)mentioning
confidence: 99%
“…Differences were found in the gender distribution and prevalence of the cardiovascular disease across classes, with patients experiencing “severe multiple symptoms” and “urinary incontinence” reporting the lowest HRQOL. It is also crucial to highlight that LUTS can have a hidden neurological cause in patients without a formally diagnosed neurological disorder (“occult neurology”) [ 9 ] or hide another underlying medical condition like cardiovascular disease or diabetes type 2 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%